The impact of maternal age on foetal growth patterns and newborn size - Kirchweger, Franziska; Kirchengast, Sylvia; Hafner, Erich; Stümpflein, Ingrid; Hartmann, Beda (Anthropological Review, 2018)
The association patterns between maternal age and foetal growth parameters as well as newborn size were analysed using a dataset of 4737 singleton term births taking place at the Viennese Danube hospital. Foetal growth patterns were reconstructed by the results of three ultrasound examinations carried out at the 11th/12th, 20th/21th and 32th/33thweek of gestation. In detail, crown-rump length, biparietal diameter, fronto-occipital diameter, head circumference, abdominal transverse diameter, abdominal anterior-posterior diameter, abdominal circumference, and femur length were determined. Birth weight, birth length and head circumference were measured immediately after birth. Young teenage mothers (≤15 years), older adolescent mothers (16-19 years), mothers of optimal age range (20-35 years) and mothers of advanced age (>35 years) differed significantly in body height, pre-pregnancy weight status and gestational weight gain. Surprisingly, the foetuses of young adolescent mothers were the largest ones during first trimester. During the second and third trimester however, the foetuses of mothers of optimal age range (20-35 years) and mothers older than 35 years showed larger biometric dimensions than adolescent mothers. According to multiple regression analyses, maternal age was significantly related to Foetal head size (ß =-0.04; 95% CI = -0,08 – 0.01; p=0.034) and abdominal dimensions (ß= 0.03; 95% CI = 0.01-0.05; p=0,011) during the second trimester and to birthweight (ß= -0.03; 95% CI= -4.40 – 0.04; p=0.050). The associations however, are quite weak and the statistical significance is maybe due to the large sample size. At the time of birth, offspring of mothers of optimal age range (20 to 35 years) is significantly larger than that of adolescent mothers and mothers of advanced age. Mothers of advanced age showed the significantly highest (p=<0.0001) prevalence (5.6%) of SGA newborns (<2500g). The small size of newborn among young adolescent mothers may be due to a competition over nutrients between the still growing mothers and the foetuses during the third trimester, while placental ageing may be responsible for smaller size of offspring among mothers of advanced age.